Irbesartan Ameliorates Lipid Deposition by Enhancing Autophagy via PKC/AMPK/ULK1 Axis in Free Fatty Acid Induced Hepatocytes - He, Juan; Ding, Jian; Lai, Qiuhua; Wang, Xinke; Li, Aimin; Liu, Side (Frontiers in Physiology, 2019)
Irbesartan has shown significant therapeutic effects in hypertensive patients with nonalcoholic fatty liver disease (NAFLD). To determine the underlying mechanisms of its action, we established an in vitro model of NAFLD by treating human and mouse hepatocytes with free fatty acids (FFAs) and angiotensin (Ang) II. Irbesartan significantly reversed AngII/FFA-induced lipid deposition and mitochondrial dysfunction by restoring ATP production and the mitochondrial membrane potential (MMP), and decreasing the levels of reactive oxygen species (ROS) and inflammatory markers. In addition, ibersartan also increased the autophagy flux, in terms of increased numbers of autolysosomes and autophagosomes, and the upregulation and mitochondrial localization of the autophagic proteins Atg5 and LC3BII/I. Activation of protein kinase C (PKC) and inhibition of the autophagic flux exacerbated mitochondrial dysfunction in the steatotic hepatocytes. Furthermore, AngII upregulated PKC which inhibited AMPK phosphorylation via direct interaction with the AngII receptor AT1-R. Irbesartan inhibited PKC and activated AMPK and its downstream effector ULK1, thereby inducing autophagy, decreasing lipid deposition, and restoring mitochondrial function. Taken together, irbesartan triggers autophagy via the PKC/AMPK/ULK1 axis to ameliorate the pathological changes in the steatotic hepatocytes.